Influence of fly ash based seed pelleting on root rhizosphere populations of sesame: FLYASH ON MICROBIAL POPULATION IN SESAME - M PRAKASH; G SATHIYA NARAYANAN; B SUNIL KUMAR (Journal of Oilseeds Research, 2019)
Sesame (Sesamum indicum L.) is one of the most ancient oilseed crops. This important annual oil seed crop has been cultivated widely for its edible oil (42-54%) and protein (22-25%). Sesame oil has two important components, sesamin and sesaminol, which play a major role in antioxidant activity. Seed pelleting is an effective, simple technique to enhance crop establishment under unfavourable environmental conditions, particularly in the case of small seeded crops like sesame. The role of rhizosphere population is important in the context of providing conducive environment and enhancing the yield of the growing plants. Fly ash is a coal combustion residue of thermal power plants. It has great potentiality in agriculture due to its efficacy in modification ofsoil health and crop performance. The high concentration of elements (K, Na, Zn, Ca, Mg and Fe) present in flyash increases the yield of many agricultural crops. The role of flyash in influencing microbial activity through increased microbial population was studied in sesame through seed pelleting technique. Field experiments were conducted with flyash @ 200, 250 and 300 g with rice gruel and gum arabic (as adhesives) to study its influence on crop growth, soil parameters and microbial population in sesame. The experimental results revealed that seed pelleting with fly ash increased crop growth, soil parameters and microbial populations of bacteria, fungi, Actinomyctes, rhizobium, Azospirillum and seed yield in sesame, when compared to other treatments.